A MODEL FOR A FUNCTIONAL AND ENTREPRENEURIAL INTERNSHIP PROGRAM FOR HOSPITALITY EDUCATION IN THE PHILIPPINES - Evangeline E. Timbang; Mary Caroline N. Castano (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The main objective of this study is to develop a functional and responsive entrepreneurial internship model for the Philippine Hospitality Management Education program. Mixed methods research design was employed using a combination of the following: a survey that contained an assessment of compliance to a checklist from the Philippines’ Commission on Higher Education [CHED] Student Internship Program in the Philippines [SIPP] Requirements, a survey questionnaire containing proposed requirements for the quantitative portion of the study, and a semi-structured interview with key informants was utilized for the qualitative side. The study showed that there were no significant differences in the level of compliance to CHED’s SIPP between autonomous and non-autonomous HEIs. Moreover, the elements of an entrepreneurial internship program namely entrepreneurial objectives, internship trainer/facilitator, pre-entrepreneurial internship stage, entrepreneurial internship stage, and post-entrepreneurial internship stage were perceived to be important but non-existent in most hospitality management internship programs.